Senoji knyga Kaune - Lūžys, Sigitas (Knygotyra, 2024)
The article centers on sets of books from Kaunas of the 17th-18th centuries. The first contacts with books in Kaunas were recorded in the 16th century when the studies of Lithuanian youth in foreign universities began. In the beginning, the inhabitants of Kaunas mainly went to the University of Cracow, so the first book which belonged to Andreae de Cawno, "Questiones de anima," was listed at Cracow University. From the middle of the 16th century, there is some knowledge about private sets of books in Kaunas. The biggest and most interesting sets of books belonged to Jonas Olandras, Jonas Savecevičius, Tomas Frezas, and Fridrikas Vongerenas. In the library of the latter, there were even works of classical authors (Virgilius, Ovidius, Martialis). The very first known text in Lithuanian in a private library is "Ewangelie polskie i litewskie" by Jonas Jaknavičius, which D. and K. Velt had in 1785. Monasteries and churches also had their libraries. Four incunabula known in Lithuania at present had belonged to monasteries or monks in Kaunas. It should be noted that at the beginning of the 18th century, among 32 books in St. Cross Church, there were works of famous Lithuanians - Mikalojus Kristupas Radvila, Žygimantas Liauksminas, Kazimieras Vijūkas-Kojalavičius. The most abundant educational library in Kaunas belonged to the Jesuits. Up to now, in the collection of KAVB, there are 78 books from the Jesuits’ library, mainly in Latin, Polish, 2 books in German, and 1 book in French. After the abolition of the Order of the Jesuits in 1773, the most valuable books were transferred to Vilnius University Library. In the middle of the 19th century, the remaining books from the Jesuits’ library in Kaunas were supplemented by the remainder of the Jesuits’ library from Kražiai.